EFIKASI DIRI, ONSET LAKTASI DAN PEMBERIAN COLOSTRUM DALAM PEMBERIAN ASI PADA NEONATUS - yuniarti, yuniarti; Zakiah, Zakiah (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2020)
United Nation International Children Education Found(UNICEF) and World Health Organization (WHO) recommend exclusive breastfeeding until 6 months old. Early provision of breast milk is highly recommended because it provides many health benefits for both mother and baby. The objective in this study was to determine the effect of maternal self-efficacy, lactation onset and Colostrum administration on breastfeeding in neonates in Banjarbaru City in 2016. The study design was an analytical survey with a Prospective Cohort approach to determine the effect of maternal self-efficacy, lactation onset and Colostrum on breastfeeding. This research was conducted in 13 Private Practice Midwives (BPM) in Banjarbaru City in 2016. The study population was all post partum mothers in BPM in Banjarbaru City, samples was post partum mothers who gave birth in BPM which was used as research sites totaling 100 respondents taken with the technique Purposive Sampling. Univariate analysis, used to determine the description of breastfeeding, self-efficacy, maternal, onset of lactation and colostrum giving. Bivariate analysis to analyze the relationship between variables used spearman Rank test with a value of α 0.05 and 95% CI. The results showed there was a relationship between giving Colostrum (p = 0.024), onset of lactation (p = 0.010) and maternal self-efficacy (p = 0,000) with breastfeeding in Banjarbaru City 2016. Suggestions for mothers who have babies to give full breast milk to the baby because breast milk is easy to provide, cheap and healthy for the baby. Keywords: breast milk, colostrum, onset of lactation and self-efficacy